M82. GROWING BURDEN OF DISEASE: THE PREVALENCE OF CHRONIC HEALTH CONDITIONS AFTER A FIRST EPISODE OF PSYCHOSIS. (18th May 2020) - Rodrigues, Myanca; Stranges, Saverio; Ryan, Bridget; Anderson, Kelly
Abstract: Background: Over 12% of Canadians live with two or more (2+) co-occurring chronic physical health conditions or multimorbidity. This proportion is expected to rise with increased exposure to risk factors for these diseases. People with psychotic disorders often have co-occurring chronic physical health conditions; however, to date there has been a paucity of research on the prevalence of multimorbidity among people with psychosis. The objective of our study was to examine the prevalence of multimorbidity ten years after a first episode of psychosis (FEP) utilizing data from a retrospective cohort study based on health administrative data. Methods: The health administrative dataset has been linked to data from the Prevention and Early Intervention Program for Psychoses in London, Canada to enable identification of FEP patients (n=455). FEP patients were compared to a randomly selected comparison group from the general population (n=1, 783), matched on age, gender, and neighbourhood. This cohort has been followed for a 10-year period in the health administrative data to ascertain the prevalence of physical comorbidities. Results: Preliminary analyses on 2, 238 patients (557 females, 1, 681 males) at 10-year follow-up, reveals that 32.1% (95% CI 28.0%, 36.5%) of FEP patients have 2+ conditions, as compared to 15.1% (95% CI 13.6%, 16.9%) of people without psychosis. Full results on risk factors for multimorbidity will be presented. Discussion: The findings from this study will facilitate increased surveillance and recognition of the common physical health conditions faced by people with psychosis, including those contributing to premature mortality of this patient population. This information aims to assist decision-makers in creating tailored intervention plans to improve the physical health of patients with psychotic disorders, and integrate care across multiple specialties to reduce the growing burden of disease to the Canadian health system.